2017
DOI: 10.3389/fpsyg.2017.01076
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Effect of Coping Style on the Relations between Personality and Life Satisfaction in Chinese Adolescents

Abstract: Previous findings showed the associations between each of the Big Five personality trait and adolescents’ life satisfaction were different. Some traits (extraversion and neuroticism) correlated with adolescents’ life satisfaction, while other traits did not have the same associations with adolescents’ life satisfaction. In order to explain why the Big Five traits differed in their associations with adolescents’ life satisfaction, the present study verified the relations between each of the Big Five personality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 105 publications
(180 reference statements)
1
13
0
Order By: Relevance
“…According to our findings, extraversion had only a direct effect on subjective well-being, which could be attributed to a higher temperamental susceptibility and stronger positive reactions of individuals high in extraversion to potential rewards in different situations and thus to more frequent experiences of positive emotions that represent an important component of subjective well-being ( Heidemeier & Göritz, 2016 ). However, extraversion may also influence subjective well-being through other possible mediators, not investigated in the present study (e.g., coping strategies; Xu et al, 2017 ). Overall, the strongest total effect on subjective well-being was observed for neuroticism, with direct and indirect negative effects both significant.…”
Section: Discussionmentioning
confidence: 78%
“…According to our findings, extraversion had only a direct effect on subjective well-being, which could be attributed to a higher temperamental susceptibility and stronger positive reactions of individuals high in extraversion to potential rewards in different situations and thus to more frequent experiences of positive emotions that represent an important component of subjective well-being ( Heidemeier & Göritz, 2016 ). However, extraversion may also influence subjective well-being through other possible mediators, not investigated in the present study (e.g., coping strategies; Xu et al, 2017 ). Overall, the strongest total effect on subjective well-being was observed for neuroticism, with direct and indirect negative effects both significant.…”
Section: Discussionmentioning
confidence: 78%
“…In fact, neuroticism alludes to individual differences in negative responses to threats (Lahey 2009), extraversion refers to positive emotions (Lucas et al 2008), openness involves attentiveness to inner feelings (Koenig et al 2012), agreeableness shapes social attitudes through trust and modesty (Costa et al 1991), and conscientiousness expresses the need for achievement and commitment (Costa et al 1991). Xu et al (2017) found a similar pattern of results. However, based on a meta-analysis of 2142 correlation coefficients derived from 347 samples, Steel et al (2008) concluded that only neuroticism, extraversion, agreeableness, and consciousness were significantly related to all subjective well-being facets measured.…”
Section: Personality and Life Satisfactionmentioning
confidence: 93%
“…However, based on a meta-analysis of 2142 correlation coefficients derived from 347 samples, Steel et al (2008) concluded that only neuroticism, extraversion, agreeableness, and consciousness were significantly related to all subjective well-being facets measured. Some other researchers (Heidemeier and Göritz 2016;Joshanloo and Afshari 2011;Stolarski and Matthews 2016;Xu et al 2017) indicated that openness to new experiences appears to be a rather weak and inconsistent correlate and/or predictor of life satisfaction. Moreover, the literature relevant to the assessment of the relationship between personality and satisfaction through regression analysis shows that personality has a strong influence on life satisfaction (Schimmack et al 2004), hedonic balance and subjective well-being (Costa and McCrae 1980).…”
Section: Personality and Life Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations